Intraoperative post‐conisation human papillomavirus testing for early detection of treatment failure in patients with cervical intraepithelial neoplasia: a pilot study. Issue 4 (27th November 2012) - Torné, A; Fusté, P; Rodríguez‐Carunchio, L; Alonso, I; del Pino, M; Nonell, R; Cardona, M; Rodríguez, A; Castillo, P; Pahisa, J; Balasch, J; Ramírez, J; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the feasibility and utility of intraoperative post‐conisation human papillomavirus (IOP‐HPV) testing and cytology to detect treatment failure in patients with cervical intraepithelial neoplasia grades 2–3 (CIN2–3). Design Prospective observational pilot study. Setting Barcelona, Spain. Population A cohort of 132 women treated for CIN2–3 by loop electrosurgical conisation. Methods An endocervical sample was obtained intraoperatively with a cytobrush from the cervix remaining after the conisation. The material was kept in PreservCyt medium and processed for Hybrid Capture 2 and cytology. Patients were followed‐up for 24 months. The performance of IOP‐HPV testing and IOP cytology was compared with conventional indicators of recurrence (cone margin, endocervical curettage, and HPV testing and cytology at 6 months). Main outcome measure Treatment failure (i.e. recurrent CIN2–3 during follow‐up). Results Treatment failure was identified in 12 women (9.1%). IOP‐HPV testing for sensitivity, specificity, and positive and negative predictive values for treatment failure were 91.7, 78.3, 62.2, and 96.0%, respectively, which are similar to the figures for conventional HPV testing at 6 months (91.7, 76.0, 64.0, and 95.1%, respectively), and are better than the values of other conventional predictive factors (cone margin, endocervical curettage, and cytology intraoperative at 6 months). IOP‐HPV was strongly associated with treatment failure in the multivariate analysis (OR 15.40, 95% CI 1.58–150.42). Conclusion IOP‐HPV testing is feasible, and accurately predicts treatment failure in patients with CIN2–3. This new approach may allow an early identification of patients with treatment failure, thereby facilitating the scheduling of an attenuated follow‐up for negative patients who are at very low risk of persistent disease.